If 3x^2-2x+7=0,then (x-1/3)^2= please help with detailed steps because i dont really understand it. I know the answer is -20/9 but please explain

Answers

Answer 1
Answer:

Answer:

-(20)/(9)

Explanation:

A quadratic function is a kind of function with highest degree 2 .  Standard form of the quadratic equation : tex]ax^2+bx+c=0[/tex]

Further explanation:

Consider the given quadratic equation : 3x^2-2x+7=0  

First we divide both sides  by 3 , we get

x^2-(2)/(3)x+(7)/(3)=0--------(1)

Compare this equation to x^2+2ax+a^2 , we have

2a=(-2)/(3)  

\Rightarrow\ a=(-1)/(3)  [divide both sides by 2]

Now using the completing the squares method , Add and subtract ((-1)/(3))^2 to the left side in (1), we get

x^2-(2)/(3)x+((-1)/(3))^2-((-1)/(3))^2+(7)/(3)=0  

It can be written as

(x^2-2((1)/(3))x+(1)/(3))^2)-(1)/(9)+(7)/(3)=0  

Use identity x^2-2ax+a^2=(x-a)^2, we have

(x-(1)/(3))^2)+(7(3)-1)/(9)=0  

(x-(1)/(3))^2)+(20)/(9)=0  

Subtract (20)/(9) from both the sides , we get

(x-(1)/(3))^2)=-(20)/(9)

Therefore, the value of (x-(1)/(3))^2)=-(20)/(9)

Learn more :

Keywords :

Quadratic equation, standard form, completing squares method, Polynomial identities.

Answer 2
Answer:

For this case we have the following polynomial:

3x^2-2x+7=0

To solve the problem, we must complete squares.

The first step is to divide the entire expression by 3.

We have then:

(3)/(3)x^2-(2)/(3)x+(7)/(3)=0

The second step is to place the constant term on the right side of the equation:

(3)/(3)x^2-(2)/(3)x=-(7)/(3)

The third step is to complete the square:

(3)/(3)x^2-(2)/(3)x + (-(1)/(3))^2=-(7)/(3)+ (-(1)/(3))^2

Rewriting we have:

x^2-(2)/(3)x + (1)/(9)=-(7)/(3)+ (1)/(9)

(x-(1)/(3))^2 = -(20)/(3)

Answer:

By completing squares we have:

(x-(1)/(3))^2 = -(20)/(3)


Related Questions

The probability of event X is 30%. The probability of event Y is 40%. If events X and Y are mutually exclusive, what is the probability of event X or Y?70%12%10%35%
The equation of line CD is (y-3) = -2(x-4). What is the slope of a line perpendicular to line CD? a. 2 b. -2 c. 1/2 d. -1/2
In at least 100 words independently write your response to the statement, "Anyone can do well in math."
Which steps should be followed to write an equivalent ratio to find 2% of 6700? Write 2% as the ratio StartFraction 200 Over 100 EndFraction. Write the equivalent ratio StartFraction question mark Over 6700 EndFraction. (100)(67) = 6700, so (20)(67) = 1340. Write 2% as the ratio StartFraction 20 Over 100 EndFraction. Write the equivalent ratio StartFraction 6700 Over question mark EndFraction. (20)(335) = 6700, so (100)(335) = 33,500. Write 2% as the ratio StartFraction 2 Over 100 EndFraction. Write the equivalent ratio StartFraction question mark Over 6700 EndFraction. (100)(67) = 6700, so (2)(67) = 134. Write 2% as the ratio StartFraction 2 Over 100 EndFraction. Write the equivalent ratio StartFraction question mark Over 6700 EndFraction. (100)(6.7) = 6700, so (20)(6.7) = 13.4
1.solve the following equation for y 3x- 2y= 62. solve the following equation 1/3(6x-9)= 3/4(4x-8)3. solve 3(2x-1)/4= x + 7/2 the 3(2x-1) is over the 4 and the x + 7 is over the 2 i really dont understand them

(−2x0y3 )(4x2y4 )+(2y5 )(3xy)2

Answers

(-2*x^0*y^3)*(4x^2y^4)+(2y^5)*(3xy)^2

-2*y^3*4x^2*y^4+2y^5*9*x^2*y^2

-2*y^3*4*x^2*y^4+2*y^5*9x^2y^2

-8x^2y^7+18*x^2*y^7

therefore

\boxed{\boxed{10*x^2*y^7}}

Step-by-step explanation:

Answered

(-2*x^0*y^3)*(4x^2y^4)+(2y^5)*(3xy)^2

-2*y^3*4x^2*y^4+2y^5*9*x^2*y^2

-2*y^3*4*x^2*y^4+2*y^5*9x^2y^2

-8x^2y^7+18*x^2*y^7

therefore

\boxed{\boxed{10*x^2*y^7}}

162 is what percent of 200

Answers

In order to find out what percentage of 200 162 is, we just need to divide 162 by 200.

162 / 200 = 0.81

To transform the decimal to a percentage, we just need to multiply it by 100.

0.81 * 100 = 81

162 is 81% of 200.
Hope that helped =)

Answer:

81%

Step-by-step explanation:

1. We assume, that 200 equals 100% -because it's the output value of the task

2. We assume, that x is the value we are looking for.

3. If 100% equals 200,so we can write it down as 100%=200

4.  We know, that x% equals 162 of the output value, so we can write it down as x% =162

5. Now we have two simple equations

1) 100%=200

2) x%=162

where the left sides of both of them have the same units, and both of the right sides have the same units, so we can do something like that:

100%/x%=200/162

6. Now we just have to solve the simple equation, and we will get the solution we are looking for.

7. the solution for 162 is what percent of 200

100%/x%=200/162

(100/x)*x=(200/162)*x  -we multiply both sides of the equation by x

100=1.234567890123*x  -we divide both sides of the equation by (1.234567890123) to get x

81%=x

x=81%

now we have:

162 is 81% of 200

hope this helps!

:D

The difference of a number q and 8

Answers

The difference of a number q and 8 is q-8.

It is required to write thedifference of a number q and 8.

What is algebra?

A part of mathematics in which letters and other general symbols are used to represent numbers and quantities in formulae and equations.

Given that:

considering the word "difference" means subtraction, so to  subtract 8 from q.

the difference of a number q and 8 is

q-8.

Therefore, the difference of a number q and 8 is q-8.

Learn more about algebra here:

brainly.com/question/652840

#SPJ2

8-q, considering the word "difference" means subtraction, so you are subtracting 8 from q.

A curve is described by the following parametric equations:x = 2 - t
y = x^2 + 1
Which statement best describes the curve?

The curve is a parabola with a vertex at (2, 1) and is traced from left to right for increasing values of t.
The curve is a parabola with a vertex at (2, 1) and is traced from right to left for increasing values of t.
The curve is a parabola with a vertex at (-2, -1) and is traced from left to right for increasing values of t.
The curve is a parabola with a vertex at (-2, -1) and is traced from right to left for increasing values of t.

Answers

When you use a parameter to describe equations then you are talking about Parametric Equations, that is, you can write both x and y as functions of a parameter t. In this problem we have the following equations:

x=2-t \n y=x^(2)+1

So substituting x in y we have:

y=(2-t)^2+1 \n y=4-4t+t^2+1 \n y=t^2-4t+5

So this equation represents a parabola where y is the dependent variable and t is the independent variable. This equation is shown in the figure below, the best statement that describes this curve is:

The curve is a parabola with a vertex at (2,1) and is traced from left to right for increasing values of t. 

A curve is described by parametric equations x = 2 - t;

y = x^2 + 1 statement the curve is a parabola with a vertex at (2,1) and is traced from left to right for increasing values of t is the best-described curve.

We use a parameter to describe equations then we are talking about Parametric Equations, that isWe can write both as functions of a parameter.

We have given the parametric equation

x = 2 - t\ny = x^2 + 1

What is the parametric equation?

The parametric equation defines a group of quantities as functions of one or more independent variables called parameters.

So substituting the value of x in y we get,

y=(2-t)^2+1\ny=2^2-4t+t^2+1\ny=4-4t+t^2+1\ny=5-4t+t^2\n

So this equation represents a parabola where y is the dependent variable and t is the independent variable.

This equation is shown in the following figure, the best statement that describes the curve.

Therefore we can say that the curve is a parabola with a vertex at (2,1) and is traced from left to right for increasing values of t.

To learn more about the parametric equation visit:

brainly.com/question/51019

What is the value of x?

Answers

We can see on the number line that the bracket is 4 units long,
and the label above it says that it's (-3x + 1) long.

-3x + 1 = 4

Subtract 1 from each side:        -3x = 3

Now divide each side by  -3 :     x = -1
|2-(-2)|=-3x+1\n\n-3x+1=|2+2|\n\n-3x+1=|4|\n\n-3x+1=4\ \ \ \ |subtract\ 1\ from\ boh\ sides\n\n-3x=3\ \ \ \ \ \ |divide\ both\ sides\ by\ (-3)\n\n\boxed{x=-1}

Rewrite in simplest terms:

10(7g-9h)-4h-8(-h+8g)10(7g−9h)−4h−8(−h+8g)

ASAP

Answers

The answer is 2(3g-43h)